The illustrated atlas of the human body - McMillan, Beverly (Weldon Owen, 2008)
Layer by layer, both the structure and function of the human body are mapped in stunning detail. Packed with body maps, lavish photography, informational diagrams and up-to-date anatomical facts, this is the ultimate guide to the human body. Each subsection concludes with a presentation of what happens when the body is invaded or malfunctions, our natural defenses, the most recent research on diagnosis and the latest medical innovations.